Applying a Differentiated Instruction Approach to Natural and Social Sciences (IPAS) Education in Elementary School - Magfirah, Magfirah; Inganah, Siti; Iswatiningsih, Daroe (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to describe the application of a differentiated approach in Natural and Social Sciences (IPAS) learning in elementary schools. This study uses a qualitative descriptive approach with a multisite study design. The data of this research consist of descriptive information related to the planning, implementation, and evaluation of differentiated instruction in the IPAS subject. The data were obtained from teachers and students who were directly involved in the IPAS learning activities. Data collection techniques in the form of observation, depth interviews, and documentation analysis. The data were analyzed using the interactive analysis model by Miles & Huberman, which includes data reduction, data display, and conclusion drawing. The subjects of the study were teachers and students from three elementary schools in Gowa Regency, South Sulawesi, namely SD Negeri Rappokaleleng, SD Inpres Tamanyeleng, and SD Negeri Tanabangka. The results show that teachers have applied a differentiated approach to three main aspects of learning: content, process, and product. In the planning stage, teachers conducted diagnostic assessments to identify students' learning styles and interests as the basis for developing flexible teaching modules. In implementation, teachers present materials in various forms and provide a choice of activities and products according to students' learning preferences. The assessment is carried out in a formative and summative manner with a varied approach and adjusted to the individual needs of the student. A differentiated approach has been proven to increase students' active participation, motivation, and independence in learning. However, its implementation still faces a number of obstacles, such as limited time, facilities, and students' readiness for independent learning. Therefore, this study recommends the importance of systemic support and teacher capacity building so that the implementation of differentiated approaches can take place in a sustainable and equitable manner in primary schools.